DOES MOTIVATION LINK JOB SATISFACTION AND WORK ENVIRONMENT TO PERFORMANCE? - Alfain, Muhammad Zain; Shidiq, Rama Fajar; Wafa, Muhammad Sirril (Jurnal Daya Saing, 2025)
This study examines the impact of the Work Environment and Job Satisfaction on Employee Performance, with Work Motivation as a mediating variable, focusing on 177 active employees in Central Java using SEM-PLS analysis. The results show that Job Satisfaction significantly enhances both Work Motivation and Employee Performance, while the Work Environment significantly affects Work Motivation but not Employee Performance directly. Work Motivation plays a crucial mediating role in linking the Work Environment and Job Satisfactio to Eemployee Performance. The findings highlight the importance of fostering Job Satisfaction and creating a supportive Work Environment to boost employee motivation and overall performance